AT-THIBAQ FI SURAH ALI-IMRAN (DIRAASAH TAHLILIYAH BALAGHIYAH) - Yulianti, Yulianti; Nurohman, Nurohman; Aeni, Resva Saprotul (Jazirah: Jurnal Peradaban dan Kebudayaan, 2023)
The reason why the researcher tested Surah Al-Quran Ali-Imran as research data is that the Qur’an contains features that other books cannot contain. Besides, it is very easy for every reader to understand the language of the Qur’an and it can be used as a way of life for every Muslim. The researchers want to explore the science of rhetoric, especially about counterpoint, because in Surat Ali-Imran, according to the researchers’ observations, there is a lot of counterpoint so the researcher wants to go deeper. Type of research In desktop research, the sources, data, and references used by the researcher in this research are taken from library materials such as books, courses, research, and other types of library sources. The method of data: clarifying the obtained data, and collecting the theory of Badi’ science in the surah in the Qur’an. And the analysis results are the application of the counterpoint in Surat Ali-Imran and an interpretation of 32 verses that include the counterpoint in the science of rhetoric that the researcher analyzes for the considerations of rhetoric science, the positive counterpoint 29 of the verse, As for Tabaq Al-Suliya, it has 7 verses. And all the dishes in this surah are 38 dishes. Thibaq forms in speech comes in four forms, namely: (1) to be two verbs (18) verses, (2) That 13 verses be two nouns, (3) That two letters are two verses (4) that Verb ayat is the noun.